Actuator fault tolerant control based on probabilistic ultimate bounds. (January 2019) - Pizzi, Noelia; Kofman, Ernesto; De Doná, José A.; Seron, Maria M.
Abstract: In this work we introduce a novel set-based fault tolerant control scheme for linear systems under Gaussian disturbances. In the proposed strategy, actuator faults are detected and diagnosed when residual trajectories enter and remain in certain sets that are computed as probabilistic ultimate bounds. After a fault is diagnosed, the control scheme is reconfigured to take into account the corresponding actuator failure and preserve certain closed loop features. We show that our strategy can detect and diagnose the different faults considered with an arbitrarily small probability of misdetection. Highlights: An actuator fault tolerant control strategy is proposed by systems with Gaussian disturbances. The occurrence of failures is detected and diagnosed when residual trajectories reach certain probabilistic sets. After a fault is diagnosed, the control scheme is reconfigured.